The Effect Of Good Corporate Governance, Profitability, and Company Size on Company Value : (Empirical Study on the Infrastructure Sector Listed on the Indonesia Stock Exchange from 2021 - 2023) - Niswah Inayah; Achmad Fauzi; Umi Widyastuti (Research Trend in Technology and Management, 2025)
The capital market plays a strategic role in accommodating public investment needs through various financial instruments while providing access to funding for companies to foster economic growth. A decline in stock value, which negatively affects the Composite Stock Price Index (IHSG), highlights the importance of examining internal factors influencing firm value. One such factor is Good Corporate Governance (GCG), which promotes sound management and increases investor confidence. Additionally, a company’s profitability reflects managerial efficiency in utilizing resources and generating sustainable profits. Firm size also serves as a key aspect, indicating the scale of operations and market competitiveness, which may contribute to increasing firm value. This research examines companies in the infrastructure sector listed on the Indonesia Stock Exchange (IDX) over the 2021–2023 period, drawing on a purposively selected sample of 28 firms and a total of 84 observations. To evaluate the impact of internal determinants on firm value, multiple linear regression analysis using a Random Effect Model (REM) was conducted via Eviews 12. Good Corporate Governance (GCG) was operationalized by employing proxies such as the proportion of managerial shareholding, institutional ownership, and the presence of independent commissioners. Profitability was represented through Return on Assets (ROA), whereas firm size was expressed using the logarithmic scale of total assets. To measure the dependent variable, firm value, the Tobin’s Q metric was applied, enabling a data-driven exploration of these internal influences. Based on the analysis results, it was found that managerial ownership and institutional ownership exert a positive and significant influence on firm value. In contrast, the independent board of commissioners and firm size demonstrate a negative and significant effect. Meanwhile, the profitability variable does not show a significant relationship with firm value. These findings contribute to enriching the empirical literature on internal factors affecting firm value and offer practical implications for both management and investors in formulating strategic decisions, particularly within the infrastructure sector.